Corrosion-resistant composition and concrete structure protection method
By using a combination of urethane resin and vinyl ester resin in corrosion-resistant coatings, and adding toughening agents and curing accelerators, the problems of cracking and poor workingability of the coating due to curing shrinkage are solved, and efficient corrosion protection is provided.
Patent Information
- Application Number
- JP2024011682
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-01-30
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-01-30
AI Technical Summary
During the use of existing corrosion-resistant coatings, there are problems such as cracking caused by curing and shrinking, poor workingability and bonding during use, especially coatings represented by vinyl ester resins are particularly obvious when no reinforcement materials are used.
Using a corrosion-resistant coating formulation containing urethane resin and vinyl ester resin, a toughening agent and a curing accelerator are added to form a low shrinkage, low bonding coating that can provide excellent workability and corrosion resistance without using reinforcement materials.
It realizes that the coating has low shrinkage, low bonding, good working performance without using reinforced materials, can effectively prevent cracking, and is suitable for protection in various corrosion environments.
Smart Images

Figure 2025018894000013 
Figure 2025018894000014 
Figure 2025018894000015
Abstract
Description
[Technical field]
[0001] The present invention relates to an anticorrosive composition and a method for protecting a concrete structure. [Background technology]
[0002] Concrete structures used in harsh environments, such as chemical tanks and sewage facilities, are usually subjected to anticorrosive coating treatment to prevent corrosion caused by chemicals, sulfuric acid, etc. One known anticorrosive coating method is a coating-type lining method in which an organic anticorrosive coating material is applied to the concrete surface to form an anticorrosive coating layer, and organic anticorrosive coating materials such as epoxy resins and vinyl ester resins have traditionally been used as the organic anticorrosive coating material. When vinyl ester resin is used as the anticorrosive coating material, glass flakes, glass mats, etc. are usually used as reinforcing materials (see, for example, Non-Patent Document 1).
[0003] Epoxy resins are excellent in that they have little cure shrinkage and do not require reinforcing materials, making them easy to work with, and have good alkali resistance. On the other hand, epoxy resins are poor in acid resistance. Furthermore, aliphatic polyamines and aromatic polyamines used as curing agents for epoxy resins can cause severe skin irritation when applied, and can cause problems such as skin rashes on the applicator.
[0004] In contrast, vinyl ester resins are generally excellent in that they have good resistance to acids, alkalis and chemicals, are less irritating to the skin, etc. On the other hand, vinyl ester resins have problems such as relatively large cure shrinkage during curing, particularly linear cure shrinkage, and generally require the use of a reinforcing material, resulting in poor workability, etc. If vinyl ester resins are used without using a reinforcing material, cracks and fissures are likely to occur after curing, which is problematic in that they are unable to exhibit the appropriate performance as a corrosion-resistant coating material. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] "Manual for Corrosion Inhibition and Prevention Technology for Sewerage Concrete Structures," compiled by the Japan Sewage Works Agency, published by the Sewerage Works Support Center, a general incorporated foundation, December 2017 Summary of the Invention [Problem to be solved by the invention]
[0006] Meanwhile, the present inventors have investigated various materials to be used in combination with vinyl ester resins, and have found that in addition to the problem of cure shrinkage during curing described above, the occurrence of tackiness after curing is a problem. If the tackiness is large, problems such as difficulty in walking on the coated surface and adhesion of dust and dirt occur, resulting in poor workability.
[0007] Therefore, an object of the present invention is to provide a vinyl ester resin-containing corrosion prevention composition that can be used as a corrosion prevention coating material without using a reinforcing material and has excellent workability, and a method for protecting a concrete structure using the same. [Means for solving the problem]
[0008] In view of the above circumstances, the present inventors have conducted extensive research and have found a corrosion-preventive composition that contains a urethane acrylate resin having a tensile elongation of 50 to 150% when cured, a vinyl ester resin having a tensile elongation of 1 to 20% when cured, paraffin, a curing agent, and a curing accelerator. Such a corrosion-preventive composition can be used as a corrosion-preventive coating material without using a reinforcing material because the curing shrinkage, especially the linear curing shrinkage, during curing is sufficiently small, and the tackiness is sufficiently small, so that the workability is excellent. Here, the "reinforcing material" refers to a reinforcing material such as glass fiber (glass flake, chopped strand mat, glass cloth, roving cloth, etc.), carbon fiber, organic fiber, etc., which are generally used to improve the strength of fiber-reinforced plastics (FRP).
[0009] The present inventors have also discovered a method for protecting a concrete structure, comprising a step of protecting the concrete structure with a corrosion-resistant coating layer formed from the above-mentioned corrosion-resistant composition. The method for protecting a concrete structure uses the above-mentioned corrosion-resistant composition, and therefore has excellent workability. Effect of the Invention
[0010] According to the present invention, it is possible to provide a vinyl ester resin-containing corrosion prevention composition which can be used as a corrosion prevention coating material without using a reinforcing material and has excellent workability, and a method for protecting a concrete structure using the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows a dumbbell-shaped specimen for tensile elongation testing. [Diagram 2] FIG. 1(a) is a front view of the tensile testing machine, and FIG. 1(b) is a side view of the tensile testing machine. [Diagram 3] 2(a) is a cross-sectional view taken along line II in FIG. 2(a), and FIG. 2(b) is a cross-sectional view taken along line II-II in FIG. 2(a). [Figure 4] (a) is a front view of a steel plate for ball tack testing, and (b) is a side view of the steel plate. [Diagram 5] FIG. 2 is a diagram showing a test plate for linear curing shrinkage testing. [Figure 6] 1(a) is a front view of a test plate for crack follow-up tests, and (b) is a side view. [Figure 7] (a) is a front view of the box culvert, and (b) is a side view. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferred embodiments of the present invention will be described in detail below, however, the present invention is not limited to the following embodiments.
[0013] The corrosion prevention composition of the present embodiment contains a urethane acrylate resin having a tensile elongation of 50 to 150% when cured, a vinyl ester resin having a tensile elongation of 1 to 20% when cured, paraffin, a curing agent, and a curing accelerator.
[0014] In this specification, "corrosion prevention" means protecting objects such as concrete, mortar, and steel plates from corrosion caused by corrosive substances such as acids, alkalis, and chemicals, particularly sulfuric acid or chemicals. In addition, in this specification, the tensile elongation of a urethane acrylate resin or vinyl ester resin when cured refers to the tensile elongation measured in accordance with JIS K 7113 for a test specimen prepared by blending an appropriate amount of a curing agent (e.g., Permec (registered trademark) N, manufactured by Nippon Yushi Kagaku Co., Ltd.) and a curing accelerator (e.g., cobalt naphthenate, cobalt octenate, etc.) with a urethane acrylate resin or vinyl ester resin and then curing at room temperature. For commercially available urethane acrylate resins and vinyl ester resins, the numerical values listed in the product information can be referenced.
[0015] The urethane acrylate resin is a resin having a urethane bond and an acrylic group. The urethane acrylate resin may be either an aromatic or aliphatic urethane acrylate resin, but is preferably an aromatic urethane acrylate resin from the viewpoints of mechanical strength, corrosion resistance, etc.
[0016] The urethane acrylate resin may be one produced by a conventional method or one that is commercially available, so long as the tensile elongation upon curing is 50 to 120%. An example of a commercially available urethane acrylate resin is U-PICA 8932 (tensile elongation: 74%) (manufactured by Japan U-PICA Corporation, aromatic urethane acrylate resin, styrene monomer content: 20% by mass). The tensile elongation of the urethane acrylate resin upon curing is preferably 50 to 100%, more preferably 60 to 90%.
[0017] The urethane acrylate resin may contain a styrene monomer. When the urethane acrylate resin contains a styrene monomer, the content of the styrene monomer may be, for example, 5 to 50% by mass. When the commercially available urethane acrylate resin contains a styrene monomer, the tensile elongation upon curing may be the tensile elongation upon curing of the urethane acrylate resin containing a styrene monomer. If necessary, the amount of the styrene monomer may be adjusted by further adding a styrene monomer to the commercially available urethane acrylate resin.
[0018] Vinyl ester resin (also called "epoxy acrylate resin") is a compound (vinyl ester) having a polymerizable unsaturated bond generated by a ring-opening reaction between an epoxy compound having a glycidyl group (epoxy group) and a carboxyl group of a carboxyl compound having a polymerizable unsaturated bond such as acrylic acid, and the compound is dissolved in a polymerizable monomer such as styrene. The vinyl ester resin is not particularly limited, and those described in "Polyester Resin Handbook" (published by Nikkan Kogyo Shimbun, 1988) or "Paint Terminology Dictionary" (edited by Shikizai Kyokai, published in 1993) can be used. Vinyl ester resins are commercially available, and for example, the "Lipoxy (registered trademark)" series manufactured by Showa Denko K.K. can be used.
[0019] The epoxy compound is preferably a compound having at least two epoxy groups in the molecule. For example, bisphenol type epoxy compounds, novolac type epoxy compounds, aliphatic type, alicyclic type, monocyclic type epoxy compounds, amine type epoxy compounds, etc. are listed. Among them, bisphenol type epoxy compounds are preferred from the viewpoint of mechanical strength, corrosion resistance, etc.
[0020] Examples of bisphenol type epoxy compounds include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol AD type epoxy compounds, bisphenol S type epoxy compounds, and brominated bisphenol A type epoxy compounds. Examples of novolac type epoxy compounds include phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, and brominated novolac type epoxy compounds. Examples of aliphatic type epoxy compounds include hydrogenated bisphenol A type epoxy compounds and propylene glycol polyglycidyl ether compounds. Examples of alicyclic epoxy compounds include alicyclic diepoxy acetal, dicyclopentadiene dioxide, vinylhexene dioxide, and glycidyl methacrylate.
[0021] Examples of carboxyl compounds having a polymerizable unsaturated bond include monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, and sorbic acid; and reaction products of dibasic acid anhydrides with alcohols having at least one unsaturated group in the molecule.
[0022] As the vinyl ester resin, one produced by a conventionally known method or a commercially available one may be used as long as the tensile elongation when cured is 1 to 20%. An example of a commercially available product is Lipoxy (registered trademark) R-806 (tensile elongation: 3.2%, heat distortion temperature: 110°C, bisphenol vinyl ester resin) (manufactured by Showa Denko KK). The tensile elongation of the vinyl ester resin when cured is preferably 1.5 to 15%, more preferably 2 to 10%.
[0023] The heat distortion temperature of the vinyl ester resin when cured is preferably 80 to 220°C, more preferably 90 to 210°C, and even more preferably 100 to 200°C. When the heat distortion temperature is within the above-mentioned predetermined range, the heat resistance of the anticorrosive composition is further improved. In this specification, the heat distortion temperature of the vinyl ester resin when cured indicates, for example, the heat distortion temperature measured in accordance with ASTM D 648 for a test specimen prepared by blending a suitable blending amount of a curing agent (e.g., Permec (registered trademark) N, manufactured by Nippon Yushi Kagaku Co., Ltd.) and a curing accelerator (e.g., cobalt naphthenate, cobalt octenate, etc.) with the vinyl ester resin and then curing at room temperature. For commercially available vinyl ester resins, the numerical values described in the product information can be referred to.
[0024] The vinyl ester resin is preferably a bisphenol type vinyl ester resin, a novolac type vinyl ester resin or a modified novolac type vinyl ester resin, and more preferably a bisphenol type vinyl ester resin, which further improves the acid resistance and alkali resistance of the corrosion prevention composition.
[0025] The urethane acrylate resin and the vinyl ester resin may each be used alone or in combination of two or more kinds.
[0026] The mass ratio of the urethane acrylate resin to the vinyl ester resin in the corrosion prevention composition is preferably from 40:60 to 90:10, more preferably from 45:55 to 85:15, and even more preferably from 50:50 to 80:20.
[0027] The total content of the urethane acrylate resin and the vinyl ester resin can be, for example, 60 mass% or more, 70 mass% or more, or 80 mass% or more of the total amount of the corrosion prevention composition (excluding fillers or thixotropic agents, if any).
[0028] The anticorrosive composition may contain a resin other than the above-mentioned urethane acrylate resin and vinyl ester resin, such as an epoxy resin, an unsaturated polyester resin, or a polyester resin.
[0029] The paraffin is not particularly limited, and for example, a styrene solution of paraffin wax known as an "air hardener" can be used. As the air hardener, for example, a styrene solution with a paraffin content of 1 to 15 mass% can be used. Examples of commercially available air hardeners include Rigolac (registered trademark) air hardener (manufactured by Showa Denko K.K.: styrene 93 to 97 mass%, solid paraffin 3 to 7 mass%), U-Pica WS series (WS-A, WS-B, WS-D, WS-E, WS-G, WS-H) (manufactured by Japan U-Pica Co., Ltd.: styrene 90 to 95 mass%, solid paraffin 5 to 10 mass%), etc.
[0030] The content of paraffin in the corrosion inhibitor composition may be, for example, 0.05 to 5 mass% based on the total amount of the corrosion inhibitor composition. From the viewpoint of achieving a high compatibility between workability and mechanical strength, the content of paraffin in the corrosion inhibitor composition is preferably 0.05 to 3 mass%, and more preferably 0.1 to 1 mass%, based on the total amount of the corrosion inhibitor composition.
[0031] When the corrosion prevention composition contains a styrene monomer derived from a urethane acrylate resin, a vinyl ester resin, an air hardener, etc., the content thereof can be, for example, 3 to 50 mass%, 4 to 45 mass%, or 5 to 40 mass%, based on the total amount of the corrosion prevention composition.
[0032] As the curing agent, for example, an organic peroxide can be used. Examples of the organic peroxide include ketone peroxides such as methyl ethyl ketone peroxide and methyl isobutyl ketone peroxide, hydroperoxides such as cumene hydroperoxide and t-butyl hydroperoxide, peroxyesters such as t-butyl peroxy octoate and t-butyl peroxy benzoate, dialkyl peroxides such as dicumyl peroxide, and diacyl peroxides such as lauroyl peroxide and benzoyl peroxide, and these may be used in combination. The amount of the curing agent added is the amount usually used, and can be, for example, 0.01 to 8 parts by mass per 100 parts by mass of the total of the urethane acrylate resin and the vinyl ester resin.
[0033] The curing accelerator is a substance that decomposes the organic peroxide of the curing agent by redox reaction and facilitates the generation of active radicals. Specific examples thereof include various metal soaps such as cobalt-based, vanadium-based, and manganese-based, amines such as dimethylaniline and dimethyl paratoluidine, quaternary ammonium salts such as dimethylbenzylammonium chloride, and β-diketones such as acetylacetone, which can also be used in combination. Examples of cobalt-based metal soaps include cobalt naphthenate and cobalt octenate. The amount of the curing accelerator added is the amount normally used, and can be, for example, 0.01 to 5 parts by mass per 100 parts by mass of the total of the urethane acrylate resin and the vinyl ester resin.
[0034] The anticorrosive composition may contain other ingredients such as fillers, thixotropic agents, and the like.
[0035] Examples of the filler include calcium carbonate, aluminum hydroxide, clay, talc, silica powder, barium sulfate, mica, glass powder, ceramic powder, perlite, etc. The content of the filler can be, for example, 20 to 50 mass% based on the total amount of the anticorrosive composition. In particular, when glass powder or ceramic powder is used as the filler, the stickiness (tack) of the anticorrosive composition itself is reduced, and the workability during application is improved.
[0036] Examples of the thixotropic agent include ultrafine silica, anhydrous silica, colloidal silica, aerosil, aluminum stearate, surface-treated bentonite, hydrogenated castor oil, etc. The content of the agent can be, for example, 1 to 30 mass% based on the total amount of the anticorrosive composition. In particular, when aerosil is used as the thixotropic agent, dripping can be prevented when the anticorrosive composition is applied to a wall.
[0037] The above-mentioned anticorrosive composition has sufficiently small cure shrinkage, particularly linear cure shrinkage, and has sufficiently small tackiness and excellent workability, and therefore can be suitably used for protecting concrete structures. Note that the term "concrete structure" refers to a general structure including concrete, mortar, etc.
[0038] The above-mentioned anticorrosive composition can be suitably used, in particular, as an anticorrosive coating material for paint-type linings, a joint material, and for resin concrete panels.
[0039] The coating-type lining method is a method characterized by forming a corrosion-resistant coating layer by coating a corrosion-resistant coating material on the surface of a concrete structure. When the above-mentioned corrosion-resistant composition is applied to the coating-type lining method, a conventionally known method can be used except that the above-mentioned corrosion-resistant composition is used as the corrosion-resistant coating material.
[0040] In the coating-type lining method, a primer layer containing a vinyl ester resin or a urethane resin, a putty material containing a vinyl ester or the like (optional), a corrosion-resistant coating layer, and a top coat layer containing an unsaturated polyester resin or a vinyl ester resin are usually formed in this order by coating on an object to be protected such as concrete, mortar, steel plate, etc. In addition to the corrosion-resistant coating layer, the above-mentioned corrosion-resistant composition may also be used for the top coat layer.
[0041] Conventionally, when two or more layers of a material containing paraffin are applied, there is a concern that the adhesion between the layers is insufficient, resulting in a problem of delamination. This is because when a material containing paraffin is applied, the paraffin rises to the surface during hardening, and when a material containing paraffin is applied again, the paraffin on the surface prevents interlayer adhesion. For this reason, a material containing paraffin is usually used only for the top coat layer, and is not used for the anticorrosive coating layer. In response to this, the present inventors have found that the above-mentioned anticorrosive composition provides sufficient interlayer adhesion even when a top coat layer is formed after the formation of a corrosion-resistant coating layer.
[0042] The anticorrosive coating layer may be formed by one application or multiple applications, for example, two or three applications. The thickness of the anticorrosive coating layer may be, for example, 0.2 to 5.0 mm or 0.5 to 2 mm. Increasing the thickness of the anticorrosive coating layer requires more applications, which increases costs, so the thickness of the anticorrosive coating layer is preferably in accordance with the required performance. In addition, the thickness of the anticorrosive coating layer is preferably as thin as possible, since this reduces workability.
[0043] The joint material is a material that can be used to fill in joints that are generated when concrete blocks are arranged, and that require corrosion protection. For example, the above-mentioned anticorrosive composition can be used as a joint material for filling joints between blocks in a prefabricated concrete block chemical tank. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The following materials were used in the examples. Urethane acrylate resin: U-PICA 8932 (tensile elongation: 74%) (manufactured by Japan U-PICA Co., Ltd., aromatic urethane acrylate resin, styrene monomer content: 20% by mass) Vinyl ester resin: Lipoxy (registered trademark) R-806 (tensile elongation: 3.2%, heat distortion temperature: 110°C, bisphenol vinyl ester resin) (Showa Denko K.K.) paraffin: Rigolac (registered trademark) air hardener (Showa Denko K.K.: styrene 93-97% by mass, solid paraffin 3-7% by mass) Hardener: Hardener 328E (manufactured by Nouryon Chemical Co., Ltd., a mixture of t-butyl peroxybenzoate and cumene hydroperoxide) Curing Accelerator: Cobalt Naphthenate Glass Mat: Glass Mat #450 Ceramic Powder: Ceramic Sand (made by Takeori Kogyosho Co., Ltd.) Thixotropic agent 1: ChemiBest FDSS-5: Mitsui Fine Chemicals Co., Ltd. Thixotropic agent 2: Aerosil 200: Manufactured by Nippon Aerosil Co., Ltd.
[0045] [Test material A] Test materials 1A to 5A were prepared by mixing urethane acrylate resin, vinyl ester resin, paraffin, hardener, and hardener accelerator in the amounts (unit: g) shown in Table 1. When preparing the test specimens, the urethane acrylate resin, vinyl ester resin, and paraffin were mixed and stirred, the hardener accelerator was added and stirred, and then the hardener was added last.
[0046] [Table 1]
[0047] The following tensile elongation test was carried out on the test materials 1A to 5A. The results are shown in Table 2.
[0048] [Tensile elongation test] Dumbbell-shaped test specimens shown in FIG. 1 (units of values in the figure: mm) were made from the above test materials 1A to 5A by the following method. Three sheets of packing tape were stacked to prepare a laminate with a thickness of 0.95 mm. The laminate was cut into the dumbbell shape shown in FIG. 1 to obtain a laminate with a dumbbell-shaped hole. A separate packing tape was attached to the surface of a steel plate to provide release curing, and the laminate with the dumbbell-shaped hole was further attached to obtain a mold for preparing a test specimen having a recess corresponding to the dumbbell-shaped hole. Test materials 1A to 5A were poured into the recess of the mold, and the mold was smoothed with a spatula. The poured test material was left at room temperature for 24 hours to harden, and then the laminate was removed to obtain a test specimen. The thickness of the test specimen was about 0.80 mm. Three test specimens corresponding to test materials 1A to 5A were prepared in the same manner. The obtained test specimen was set in the tensile tester shown in Fig. 2 and Fig. 3 (unit of values in the figure: mm), and a tensile elongation test was performed. Fig. 2(a) is a front view of the tensile tester, and Fig. 2(b) is a side view of the tensile tester. The tensile tester includes a fixed table, a movable table attached so as to be movable laterally on the fixed table, and a pair of test specimen fixing plates installed on the fixed table and the movable table, respectively. Fig. 3(a) is a cross-sectional view taken along line II in Fig. 2(a), which shows the test specimen fixing plate portion on the fixed table side of the tensile tester. Fig. 3(b) is a cross-sectional view taken along line II-II in Fig. 2(a), which shows the test specimen fixing plate portion on the movable table side of the tensile tester. As can be seen from these cross-sectional views, the test specimen can be sandwiched and fixed between the fixed table and the movable table and the test specimen fixing plate. The movable table is attached to the fixed table so that it can be manually moved laterally by rotating the screw shaft via a rotary joint, and vertical vibration during movement is prevented by a movable table vibration stopper. The test specimen was fixed to this tensile tester so that 30 mm from each end of the longitudinal direction of the test specimen was sandwiched between the fixed table, the movable table, and the test specimen fixing plate. The screw shaft was rotated to move the movable table laterally at a moving speed of about 13 to 14 mm / min until the test specimen broke. The length of the part of the test specimen that was not sandwiched between the test specimen fixing plates when the test specimen was fixed to the tensile tester (the distance from the end of the test specimen fixing plate on the fixed table to the end of the test specimen fixing plate on the movable table) was defined as the "gauge length of the test specimen: L 0 (mm)", the increase in the length of the test specimen when it breaks (the distance from the end of the test specimen fixing plate on the fixed table to the end of the test specimen fixing plate on the moving table at the time of breakage, L 0 The increase in the gauge length of the test piece: ΔL 0 (mm) and tensile elongation (ΔL 0 / L 0 ) was sought.
[0049] This tensile elongation test is similar to the method of JIS K 7113, but the thickness of the test specimen was set to about 0.80 mm in order to confirm that sufficient elongation is maintained even when the coating film is made thinner. The higher the tensile elongation measured in this test, the better the workability, and for example, if it is 10% or more, it has excellent crack tracking properties even without using reinforcing materials, and it becomes possible to sufficiently prevent cracks and chasms.
[0050] [Table 2]
[0051] From the above, it was confirmed that the test materials 2A to 4A of the present invention have sufficient tensile elongation.
[0052] [Test material B] Test materials 1B to 8B were prepared by mixing urethane acrylate resin, vinyl ester resin, paraffin, hardener, and hardener accelerator in the amounts (unit: g) shown in Table 3. When preparing the test specimens, the urethane acrylate resin, vinyl ester resin, and paraffin were mixed and stirred, the hardener accelerator was added and stirred, and then the hardener was added last.
[0053] [Table 3]
[0054] The test materials 1B to 8B were subjected to the ball tack test shown below. The results are shown in Table 4.
[0055] [Ball tack test] A steel plate measuring 500 mm in length, 900 mm in width, and 5 mm in thickness was prepared. Test materials 1B to 8B were applied to the 100 mm x 100 mm areas indicated by numbers 1 to 5 in Fig. 4(a), respectively, and left to harden at room temperature for 6 hours or 24 hours to obtain test specimens. The steel plate was fixed at a 20° inclination as shown in Figure 4(b) and a ball tack test was performed. Specifically, a test ball was slid from a position 100 mm from the top end of the test specimen, and it was confirmed whether the test ball would stop on the test specimen. Specifically, 31 types of test balls with diameters ranging from 1 / 16 to 1 inch were prepared, and the test balls were slid in order from smallest to largest, and the size of the test balls when they stopped on the test specimen for 5 seconds was recorded. The same test was performed three times. Thirty-one types of test balls between 1 / 16 and 1 inch were numbered in order starting from number 1, and the average of the numbers corresponding to the size of the test balls when they stopped for the three tests was evaluated as the ball tack test result. For example, the evaluation of test material 1B after leaving it for 24 hours was as follows: 1st test: 7 / 16 (number: 14), 2nd test: 13 / 32 (number: 13), 3rd test: 3 / 8 (number: 12), so the average "13.0" was recorded as the test result. A test result of "0" indicates that no test balls stopped on the test specimen. A test result of "x" indicates that the test was not performed because the surface of the test specimen was not sufficiently hardened.
[0056] This ball tack test is in accordance with JIS Z0237: 2009. A test result of "0" means that there is almost no stickiness (tack), and the material has excellent workability.
[0057] [Table 4]
[0058] From the above, the test materials 6B to 8B of the present invention are sufficiently cured in a relatively short time of 6 hours, and have sufficiently low tackiness, making them excellent in workability. On the other hand, the test materials 1B to 4B that do not contain paraffin (air hardener) and the test material 5B that does not contain vinyl ester resin are highly tacky and have poor workability.
[0059] [Test material C] Test materials 1C to 12C were prepared by mixing urethane acrylate resin, vinyl ester resin, paraffin, hardener, and hardener accelerator in the amounts (unit: g) shown in Table 5. When preparing the test specimens, the urethane acrylate resin, vinyl ester resin, and paraffin were mixed and stirred, the hardener accelerator was added and stirred, and then the hardener was added last.
[0060] [Table 5]
[0061] [Cure shrinkage test] The test materials 1C to 12C were subjected to the cure shrinkage test shown below. Note that the test material 11C using glass mat #450 corresponds to the conventional product. The results are shown in Table 6.
[0062] <Method for measuring specific gravity before hardening> The specific gravities of test materials 1C to 12C before hardening were measured according to the following procedure. Equipment used: Platform balance (Shimadzu ELB600), specific gravity cup (BEVS 50ml) Measure the amount of material listed in Table 5 on a platform balance. Pour water or a sample into the density cup. When the water or sample overflows from the hole in the center of the density cup lid, the density cup is considered to be full. Wipe off the overflowing water or sample. The specific gravity before hardening is calculated using the following formula. S = (m3-m1) / (m2-m1) (In the formula, S represents the specific gravity of the sample (test material), m1 represents the mass of the specific gravity cup, m2 represents the mass of the specific gravity cup and water, and m3 represents the mass of the specific gravity cup and the sample.)
[0063] <Preparation of post-curing test specimens> Test materials 1C to 12C were mixed and stirred according to the procedure described below, and then applied in the form of a rectangular column or a flat plate, and after hardening, test specimens were prepared. The rectangular column-shaped specimens are made by pouring the test material into a 10x10x100mm plastic casting mold. For test materials 11C and 12C, 11 sheets of glass mat #450 cut to 18x98mm are stacked in a plastic casting mold, and the test material is poured in to make the specimens. Three block-shaped specimens are made for each type. Flat specimens are made using a 100 x 100 x 1 mm curing mold on an iron plate. For test materials 1C to 10C, the test specimens are made by pouring the test material into the curing mold and scraping it off with a metal spatula. For test materials 11C and 12C, glass mat #450 is cut to a size of 98 x 98 mm and placed in the curing mold, after which the test materials other than the glass mat are poured in and the glass mat and resin are layered to make the test specimen. Three flat specimens of each type are also made. After preparation of both the rectangular column-shaped and flat plate-shaped specimens, they were cured at room temperature for three days.
[0064] <Measurement of specific gravity after hardening> The specific gravity of the test specimen after hardening was measured according to the procedure described below. Equipment used: Platform scale (Shimadzu ELB600) To measure the specific gravity after hardening, use the specific gravity measurement mode of a platform scale. When using this mode, it is necessary to measure the weight in air and in water, so make the following preparations so that the weight in water can be measured with a platform scale. Attach a hook for underwater measurements to the back of the platform scale, hang a Φ0.18 mm wire on the hook, and attach a tray to the lower end of the wire. Place the tank filled with water so that the saucer is submerged. The specific gravity after hardening is calculated using the formula below. With this platform scale, the air weight of the test specimen is measured on the upper pan, then the test specimen is moved to the underwater tray and its weight in water is measured; the scale automatically calculates and displays the specific gravity on the display. Specific gravity after curing = weight in air / (weight in air - weight in water)
[0065] <Calculation of cure shrinkage rate> The cure shrinkage was calculated by the following formula using the specific gravity of each specimen before and after cure. Note that the specific gravity before and after cure were each the average value of three specimens. Cure shrinkage rate (%) = (specific gravity after curing - specific gravity before curing) ÷ specific gravity after curing x 100
[0066] [Table 6]
[0067] From the above, it was confirmed that the test materials 7C to 9C of the present invention had sufficiently low cure shrinkage rates compared to the conventionally used test material 11C.
[0068] [Test material D] Test materials 1D to 5D were prepared by mixing urethane acrylate resin, vinyl ester resin, paraffin, hardener, and hardener accelerator in the amounts (unit: g) shown in Table 7. When preparing the test specimens, the urethane acrylate resin, vinyl ester resin, and paraffin were mixed and stirred, the hardener accelerator was added and stirred, and then the hardener was added last.
[0069] [Table 7]
[0070] [Linear cure shrinkage test] The linear curing shrinkage of test materials 1D to 5D was measured according to the following procedure. The results are shown in Table 8.
[0071] <Preparation of test plate> The test plate shown in Figure 5 was prepared. In Figure 5, the outer frame indicates the iron plate, the inner frame indicates the part where the test material is applied (coating surface), and between the outer and inner frames, packing tape is layered to a thickness of 1 mm to form a protective mold. The iron plate is 3.2 mm thick, 300 mm wide (A in the figure), and 75 mm high (B in the figure). The coating surface is 280 mm wide (C in the figure) and 35 mm high (D in the figure). Two engravings are formed on the coating surface with a distance of 200 mm between the engravings (E in the figure). A release agent is applied to the coating surface. Three test specimens of each type are prepared.
[0072] <Preparation of test specimen> Hardened test specimens were prepared from test materials 1D to 5D using the procedure described below. For test materials 1D and 3D to 5D, after mixing, apply to the coating surface of the test plate and cut with a metal spatula until the thickness is uniform to create a test specimen. For test material 2D, cut glass mat #450 to 280 x 35 mm and place in a curing mold, then pour in the test materials other than the glass mat, and layer the glass mat and resin to create a test specimen. Three test specimens will be prepared for each test. After the test specimens are prepared, they are left to harden at room temperature for six days.
[0073] <Measurement of Linear Curing Shrinkage> After the test specimen has hardened and cured, it is carefully removed from the steel plate without applying any load to it, and it is confirmed that the markings have been transferred to the test specimen. The distance between the transferred markings is measured with a length measuring device. The linear shrinkage is calculated from the distance between the markings transferred to the test specimen and the distance between the markings on the test plate used. The linear hardening shrinkage is the average value for the three test specimens.
[0074] [Table 8]
[0075] It was confirmed that, according to the test materials 3D to 5D of the present invention, the linear curing shrinkage was reduced to the same extent as that of the conventionally used test material 2D.
[0076] [Test material E] Test materials 1E' to 5E' and 1E to 5E were prepared by mixing urethane acrylate resin, vinyl ester resin, hardener and hardener accelerator in the amounts (unit: g) shown in Table 9. Test materials 1E' to 5E' were used as casting resins, and test materials 1E to 5E were used as top coats, with the same resin numbers, for example, test material 1E' and test material 1E, being used in combination. When preparing the test specimens, the urethane acrylate resin, vinyl ester resin and paraffin were mixed and stirred, the hardener accelerator was added and stirred, and finally the hardener was added.
[0077] [Table 9]
[0078] <Preparation of test specimens for measuring sulfuric acid resistance, alkali resistance, and organic acid resistance> Test specimens for measuring sulfuric acid resistance, alkali resistance, and organic acid resistance were prepared using test materials 1E' to 5E' and 1E to 5E. Specifically, test materials 1E' to 5E' were poured as casting resin into a mold of 50 (height) x 30 (width) x 5.0 (thickness) (mm) and then cured. After curing, test materials 1E to 5E were applied as top coats with a brush to the test specimens that were removed from the mold and then cured to obtain the cured bodies. The obtained test specimens were evaluated for sulfuric acid resistance, alkali resistance, and organic acid resistance by the following methods.
[0079] <Evaluation of sulfuric acid resistance, alkali resistance, and organic acid resistance> The sulfuric acid resistance was evaluated by immersing the above-mentioned test specimens in a 33% sulfuric acid aqueous solution for 21 days and then analyzing the condition of the test specimens. The results are shown in Table 10. The alkali resistance was evaluated by immersing the specimens in a saturated solution of calcium hydroxide for 48 days and then analyzing their condition. The results are shown in Table 11. The organic acid resistance was evaluated by immersing the above-mentioned test specimens in a 30% aqueous solution of acetic acid (room temperature 20 to 30°C) for 28 days and analyzing the condition of the test specimens thereafter. The results are shown in Table 12. The evaluation was carried out based on the following criteria for swelling, cracking, softening, weight change rate, and shape change rate of the coating of the test specimen. Softening: ◎ No softening ○ Slightly softened △ Slightly softened × Softening Appearance: ◎No change○Slightly larger △Slightly larger×Larger Blisters and air spots: ◎ None ○ Very little △ A little × Many Weight change rate: Calculated based on the following formula. Weight change rate (%) = {(weight after test) - (weight before test)} ÷ (weight after test) × 100 Shape change rate: Calculated based on the following formula. Shape (length) change rate (%) = {(height + width + thickness after test) - (height + width + thickness before test)} ÷ (height + width + thickness after test) x 100
[0080] [Table 10]
[0081] [Table 11]
[0082] [Table 12]
[0083] From these results, it was confirmed that the test materials 2E to 4E of the present invention have sufficient acid resistance, alkali resistance, and chemical resistance. In particular, among the above-mentioned evaluations, the organic acid resistance is difficult to satisfy even with epoxy resins used in conventional coating-type lining methods, and it is understood that the anticorrosive composition of the present invention is superior in this respect as well.
[0084] <Preparation of specimens for adhesion tests> Test specimens for evaluating the adhesion of paraffin-containing materials, particularly when the anticorrosive composition of the present invention is applied in two or more layers, were prepared by the method described below.
[0085] A standard concrete plate is used as the test plate. The size is 300mm x 300mm x 60mm, and the application area is 0.09m. 2 The surface to be coated is roughened with a diamond cup. A one-component urethane primer (UM-50P: manufactured by Showa Denko) is applied to the roughened surface to form a primer layer. The amount of primer applied is 18 g. This is 0.2 kg / m 2 is equivalent to. After drying the primer layer for 1 hour, mix and stir urethane acrylate resin (30.0 g), vinyl ester resin (10.0 g), paraffin (2.8 g), hardener (0.60 g) and hardener accelerator (0.20 g), and apply this onto the primer layer with a brush to form an undercoat layer (corresponding to the anticorrosive coating layer). After the undercoat layer has dried and hardened for 2 hours, the components are mixed and stirred in the same ratio as for the undercoat layer, and this is applied onto the undercoat layer with a brush to form a topcoat layer. After forming the topcoat layer, the test specimen is completed after hardening and curing at room temperature for at least 24 hours.
[0086] <Adhesion test> An adhesion test was carried out by the following method. Place adhesion test attachments (steel, 40mm x 40mm) on the test specimen in four places. Paraffin will adhere to the surface of the specimen, preventing the attachment from adhering, so lightly sand the installation area with sandpaper to remove the paraffin and clean it. Sand the adhesive surface of the attachment (40mm x 40mm) with sandpaper and degrease it with a cleaner. Apply gelatinous Aron Alpha to the adhesive surface of the attachment and press it into place to adhere it. After hardening (24 hours), make cuts around the attachment with a diamond cutter and clean it. Attach the adhesion tester, rotate the handle of the tester, and apply a load until the test specimen breaks. Maximum load at break and load / mm 2 will be displayed digitally so record it.
[0087] The test was performed four times, and the average adhesion strength of the test specimens was 4.48N / mm 2 In both cases, the base material (concrete plate) was destroyed. The average bond strength was within the specified value (1.5N / mm 2 This is nearly three times the value of the conventional adhesive (above), and it was confirmed that the adhesive strength is sufficient for practical use.
[0088] In the past, when two or more layers of a material containing paraffin were applied, there was concern that the adhesion between the layers would be insufficient, resulting in the problem of delamination. This is because when a material containing paraffin is applied, the paraffin rises to the surface as it hardens, and when more material containing paraffin is applied, the paraffin on the surface prevents the layers from adhering to each other. On the other hand, in the test specimens of the present invention, paraffin rose to the surface of the undercoat layer when the undercoat layer hardened, but after the topcoat layer was formed, the paraffin contained in the undercoat layer rose to the surface of the topcoat layer together with the paraffin contained in the topcoat layer, which is presumably why sufficient interlayer adhesion was obtained.
[0089] [Crack follow-up test] A crack tracking test was conducted in accordance with the method stipulated in the Architectural Institute of Japan 2004 1560 Waterproofing Material Base Crack Tracking Test Part 2. Specifically, a crack tracking test was conducted using test material 3D according to the following procedure.
[0090] <Test fixture> A test jig was prepared consisting of a 6 mm steel plate, with an opening in the center to accommodate cracks in the test plate, and a sheath-shaped sliding type. The clearance of the sliding part was adjusted to prevent out-of-plane and in-plane displacement during testing. Both ends were shaped so that the jig could be fixed with the chuck of the testing machine. The test plate is fixed in place by tightening eight M8 cap bolts. The testing machine used is the SHIMAZU Autograph AG-I 250KN.
[0091] <Test plate> The test plate is a flexible plate (JIS A5403) with a thickness of 8 mm. The size is 80 x 200 mm, and a 6 mm deep cut is made on the back of the center to induce cracks. As with JSCE-K532, cracks are generated before the test specimen is made. After the test specimen is made, it is fixed to the test jig with eight M8 cap bolts. The front and side views of the test plate are shown in Figure 6(a) and (b), respectively.
[0092] <Preparation of test specimen> The test specimens were prepared according to the following procedure. The test plate is fixed to a steel plate of the same size with bolts and made level. As the fixing bolts will get in the way when constructing the test specimen, the test specimen and steel plate are fixed with packing tape and the bolts are then removed. A 0.8mm thick barrier is provided at the position on the test plate where the test specimen will be prepared. A one-component urethane primer is applied and allowed to dry to the touch, after which test material 3D is applied and a plastic plate (2mm thick) is placed on the test specimen and allowed to harden in order to ensure a uniform coating thickness (0.8mm). After curing at room temperature for 48 hours, the plastic plate is removed from the mold. The specimens are then cured for a further 120 hours at room temperature to prepare the test specimens. Three specimens of each type were prepared.
[0093] <Crack follow-up test> The test specimens were cured in a test room at room temperature of 23°C from the day before the test. After curing, the test specimens were tested using a testing machine (SHIMAZU Autograph). The test speed was 5 mm / min. The average value for the three test specimens was 0.8 mm. From these results, it was confirmed that the test material 3D of the present invention has excellent crack tracking properties and can be suitably applied to coating-type lining construction, etc.
[0094] [Design of coating-type lining method and testing according to quality standard C] Test specimens made using test material 3D were subjected to tests in accordance with the design and quality standard Class C of the 5.7 paint-type lining method in Non-Patent Document 1. In the following tests, the test specimens were made of plate-shaped substrates of specified material and dimensions, with one or both sides (six sides) coated with a one-component urethane primer (UM-50p: made by Showa Denko) at 0.2 kg / m 2 , Test material 3D is 0.3kg / m 2 , Test material 3D is 0.3kg / m 2 , and test material 3D at 0.2 kg / m 2 The results are shown below.
[0095] <Flow acid resistance> A test specimen was prepared by coating six surfaces of a 150 x 70 x 20 mm cement mortar plate with a one-component urethane primer and test material 3D. The test specimen was immersed in a 10% aqueous sulfuric acid solution for 45 days, and the appearance of the coating was observed. No swelling, cracking, softening, or elution was observed in the coating.
[0096] <Sulfur penetration depth> A 150 x 70 x 20 mm cement mortar plate was used as the plate-shaped substrate, and a test specimen was prepared by applying a one-liquid urethane primer and test material 3D to six sides of the plate-shaped substrate. The sulfur penetration depth was measured after immersing the test specimen in a 10% sulfuric acid aqueous solution for 120 days. The results showed that the sulfur penetration depth was 4% of the design thickness, and the penetration depth was 14 μm.
[0097] <Water permeability> The plate substrate is a regular octagon (159 cm 2 A test specimen was prepared by applying a one-component urethane primer and test material 3D to one side of the flexible board of 6 mm thick made of 100% ethylenediaminetetraacetate. When the test specimen was subjected to a water permeability test, the amount of water permeated was 0.00 g.
[0098] <Adhesion stability> A 70 x 70 x 20 mm cement mortar plate was used as the plate-shaped substrate, and a test specimen was prepared by applying a one-component urethane primer and test material 3D to one side. The integrity of this test specimen with the concrete (cement mortar) was evaluated. As a result, the standard condition had a strength of 2.9 N / mm 2 and 3.2N / mm when water is absorbed. 2 It was.
[0099] <Appearance> A test specimen was prepared by using a 200 x 150 x 6 (mm) flexible plate as the plate-shaped substrate, and coating one side with a one-component urethane primer and test material 3D. When the appearance of the coating layer of this test specimen was observed, no wrinkles, unevenness, peeling, or cracks were found in the coating.
[0100] <Alkaline resistance> A test specimen was prepared by coating six surfaces of a 150 x 70 x 20 mm cement mortar plate with a one-component urethane primer and test material 3D. The test specimen was immersed in a saturated aqueous solution of calcium hydroxide for 45 days, and the appearance of the coating was observed. No swelling, cracking, softening, or elution was confirmed in the coating.
[0101] <Organic acid resistance> A test specimen was prepared by coating six surfaces of a 150 x 70 x 20 (mm) cement mortar plate as the plate-shaped substrate with a one-component urethane primer and test material 3D. This test specimen was immersed in a 10% aqueous acetic acid solution (23°C ± 2°C) for 60 days, and the appearance of the coating was observed. No swelling, cracking, softening, or elution was confirmed in the coating.
[0102] From these results, it was confirmed that the anticorrosive composition of the present invention has sufficient acid resistance, alkali resistance, and chemical resistance. In particular, among the above-mentioned evaluations, the organic acid resistance is difficult to satisfy even with epoxy resins used in conventional coating-type lining methods, and it can be seen that the anticorrosive composition of the present invention is superior in this respect as well. The above results satisfy Class C of the design and quality standard for 5.7 coating-type lining methods.
[0103] [Construction experiment to observe adhesion, shape change, etc.] A concrete structure (box culvert) was used as the test substrate (construction base concrete) and actual coating was carried out. First, a box culvert as shown in Fig. 7 was prepared. Fig. 7(a) is a front view of the box culvert, and Fig. 7(b) is a side view of the box culvert. The box culvert shown in Fig. 7 is a box-shaped structure with an outer width of 1800 mm, an outer height of 1750 mm, an effective length of 2000 mm, and a thickness of 175 mm, and its nominal dimensions are 1100 mm x 1100 mm, and the corbel is 212.13 mm. Coating was carried out from the inner right wall to the inner ceiling of this box culvert, and the adhesion force, changes in shape, etc. were observed over time.
[0104] The application was carried out by polishing the inner concrete surface of the box culvert, and then applying a one-component urethane primer (UM-50p: made by Showa Denko) at 0.15 kg / m 2 , vinylester resin putty (3 types of base material adjustment) 0.5kg / m 2 , Test material 1F is 0.4 kg / m 2 (Undercoat), Test material 1F 0.4 kg / m 2 (Intermediate coat), Test material 1F 0.4kg / m 2 (Top coat), Test material 2F 0.15 kg / m 2 The vinyl ester resin putty was applied on a sunny day with a temperature of 33°C and a humidity of 69%, and the undercoat, intermediate coat, top coat, and top coat were applied on the following day on a sunny day with a temperature of 35°C and a humidity of 60%.
[0105] The vinyl ester resin putty used was a mixture of the following materials. Vinyl ester resin: 100.0g Curing accelerator: 0.4g Ceramic powder: 50.0g Thixotropic agent 1: 3.5g Hardener: 0.8g
[0106] Test material 1F was made by blending the materials shown below. Vinyl ester resin: 100.0g Urethane acrylate resin: 200.0g Curing accelerator: 1.2g Thixotropic agent 2: 12.0g Hardener: 2.4g Paraffin: 12.0g
[0107] Test material 2F was a mixture of the materials shown below. Vinyl ester resin: 100.0g Urethane acrylate resin: 200.0g Curing accelerator: 1.2g Paraffin: 12.0g Hardener: 2.4g
[0108] The vinyl ester resin putty is smooth and easy to work with, has a high filling rate into water pockmarks (large and small depressions on the concrete surface), and has a short hardening time of around 30 minutes. The undercoat, intermediate coat, top coat, and top coat were applied with a roller, and were soft, stretchy, and easy to work with. Its very smooth properties made it possible to achieve an even coating thickness. The material's pot life was around 10 minutes, and the hardening time was around 30 minutes, meaning that the next coating process could be carried out 30 minutes after application was complete.
[0109] On the 47th and 144th days after application, the entire coated surface was subjected to a test hammer tapping test and visual inspection. No lifting, peeling, or cracks due to linear shrinkage had occurred. There was also no change in appearance such as discoloration.
Claims
1. The corrosion prevention composition contains a urethane acrylate resin having a tensile elongation of 50 to 150% when cured, a vinyl ester resin having a tensile elongation of 1 to 20% when cured, paraffin, a curing agent, and a curing accelerator.
2. The corrosion prevention composition according to claim 1, wherein a mass ratio of the urethane acrylate resin to the vinyl ester resin in the corrosion prevention composition is 40:60 to 90:
10.
3. The corrosion-preventive composition according to claim 1 or 2, wherein the content of the paraffin is 0.05 to 5 mass% based on the total amount of the corrosion-preventive composition.
4. The corrosion prevention composition according to claim 1 or 2, which is used for protecting a concrete structure.
5. A method for protecting a concrete structure, comprising a step of protecting the concrete structure with an anticorrosive coating layer formed from the anticorrosive composition according to claim 1 or 2.
Citation Information
Patent Citations
Epoxy(METH)acrylate and its production
JP1998101753A
Primer composition for concrete
JP1998279831A
Composition for primer
JP2004352780A
Laminate with hard coat layer
JP2010058476A
Fluorine-containing curable resin and active energy ray-curable composition using the same
JP2011256330A